The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4103/jos.jos_10_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of airway dimensions in skeletal Class I malocclusion patients with various vertical facial patterns: A cephalometric study in a sample of the Saudi population

Abstract: OBJECTIVE: To compare airway widths among skeletal Class I malocclusion patients with different vertical facial patterns. MATERIAL AND METHODS: A total of 103 lateral cephalograms of skeletal Class I patients (mean age of 20 ± 2.3 years) with no history of orthodontic treatment, trauma, facial syndromes, or nasopharyngeal dysfunction were included. Based on the Frankfort–mandibular plane angle measurements, the sample was divided into three groups: low-angle, high-angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…18 In the present study, the mean upper airway space dimensions were not significantly different (p=0.201) in individuals with class I malocclusion having different vertical facial height (low angle, normal or high angle). However, Alfawazan, 19 in his study concluded that the individuals with a high angle vertical facial pattern had statistically significant narrow upper airway widths compared to those with low or normal angle (p=0.013, p=0.021, respectively). Also, Shastri et al revealed that pharyngeal length was larger in low angle subjects than in high angle subjects.…”
Section: Discussionmentioning
confidence: 93%
“…18 In the present study, the mean upper airway space dimensions were not significantly different (p=0.201) in individuals with class I malocclusion having different vertical facial height (low angle, normal or high angle). However, Alfawazan, 19 in his study concluded that the individuals with a high angle vertical facial pattern had statistically significant narrow upper airway widths compared to those with low or normal angle (p=0.013, p=0.021, respectively). Also, Shastri et al revealed that pharyngeal length was larger in low angle subjects than in high angle subjects.…”
Section: Discussionmentioning
confidence: 93%
“…In conclusion, 3D analysis of soft tissue morphology can provide valuable insights into the relationship between soft tissue characteristics and airway dimensions [9]. In relation to the dimensions of the upper airways, the study by Alfawzan indicates that the angular orientation of the mandible can also influence these dimensions [10]. Statistically significant differences were found in airway dimensions among patients with different values of the Frankfort Mandibular Plane Angle (FMA).…”
Section: Discussionmentioning
confidence: 98%
“…McNamara proposed an airway analysis to evaluate the widths of the upper and lower pharyngeal airways [17] , facilitating the study of these in a superficial manner [18] , a tendency to smaller airway dimensions has been observed in younger patients with female gender of skeletal class II [19] . The McNamara measurement is obtained by analyzing the position and morphology of the structures of the facial skeleton looking for a relationship between the upper and lower jaw with respect to the base of the skull, evaluating the intermaxillary relationship with the vertical dimension, its main purpose is to obtain differences between the skeletal and dento-alveolar components using the triangle called with the same name [5,18] .…”
Section: Mcnamara Cephalometrymentioning
confidence: 99%